The density distribution and physical origins of intermittency in supersonic, highly magnetized turbulence with diverse modes of driving - Beattie, James R.; Mocz, Philip; Federrath, Christoph; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2022)
The probability density function (PDF) of the logarithmic density contrast, s = ln (ρ/ρ0), with gas density ρ and mean density ρ0, for hydrodynamical supersonic turbulence is well known to have significant non-Gaussian (intermittent) features that monotonically increase with the turbulent Mach number, $\mathcal {M}$. By studying the mass- and volume-weighted s-PDF for an ensemble of 36 sub-to-trans-Alfv́enic mean-field, supersonic, isothermal turbulence simulations with different modes of driving, relevant to molecular gas in the cool interstellar medium, we show that a more intricate picture emerges for the non-Gaussian nature of s. Using four independent measures of the non-Gaussian components, we find hydrodynamical-like structure in the highly magnetized plasma for $\mathcal {M} \lesssim 4$. However, for $\mathcal {M} \gtrsim 4$, the non-Gaussian signatures disappear, leaving approximately Gaussian s-statistics - exactly the opposite of hydrodynamical turbulence in the high-$\mathcal {M}$ limit. We also find that the non-Gaussian components of the PDF increase monotonically with more compressive driving modes. To understand the $\mathcal {M} \lesssim 4$ non-Gaussian features, we use one-dimensional pencil beams to explore the dynamics along and across the large-scale magnetic field, $\mathrm{{\boldsymbol {B}}}_0$. We discuss kinetic, density, and magnetic field fluctuations from the pencil beams, and identify physical sources of non-Gaussian components to the PDF as single, strong shocks coupled to fast magnetosonic compressions that form along $\mathrm{{\boldsymbol {B}}}_0$. We discuss the Gaussianization of the $\mathcal {M} \gtrsim 4$s-fields through the lens of two phenomenologies: the self-similarity of the s-field and homogenization of the dynamical time-scales between the over- and underdense regions in the compressible gas.
Gesehen am 27.01.2023